Sedative and antinociceptive effects of different combinations of detomidine and methadone in standing horses - Gozalo-Marcilla, Miguel [UNESP] (2017)
Objective To evaluate intravenous (IV) detomidine with methadone in horses to identify a combination which provides sedation and antinociception without adverse effects. Study design Randomized, placebo-controlled, blinded, crossover. Animals A group of eight adult healthy horses aged (mean ± standard deviation) 7 ± 2 years and 372 ± 27 kg. Methods A total of six treatments were administered IV: saline (SAL); detomidine (5 μg kg−1; DET); methadone (0.2 mg kg−1; MET) alone or combined with detomidine [2.5 (MLD), 5 (MMD) or 10 (MHD) μg kg−1]. Thermal, mechanical and electrical nociceptive thresholds were measured, and sedation, head height above ground (HHAG), cardiopulmonary variables and intestinal motility were evaluated at 5, 15, 30, 45, 60, 75, 90, 120 and 180 minutes. Normal data were analyzed by mixed-model analysis of variance and non-normal by Kruskal–Wallis (p < 0.05). Results Nociceptive thresholds in horses administered methadone with the higher doses of detomidine (MMD, MHD) were increased above baseline to a greater degree and for longer duration (MMD: 15–30 minutes, MHD: 30–60 minutes) than in horses administered low dose with methadone or detomidine alone (MLD, DET: 5–15 minutes). No increases in nociceptive thresholds were recorded in SAL or MET. Compared with baseline, HHAG was lower for 30 minutes in MMD and DET, and for 45 minutes in MHD. No significant sedation was observed in SAL, MET or MLD. Intestinal motility was reduced for 75 minutes in MHD and for 30 minutes in all other treatments. Conclusions Methadone (0.2 mg kg−1) potentiated the antinociception produced by detomidine (5 μg kg−1), with minimal sedative effects. Clinical relevance Detomidine (5 μg kg−1) with methadone (0.2 mg kg−1) produced antinociception without the adverse effects of higher doses of detomidine.